Leishmanicidal activity of Brosimum glaziovii (Moraceae) and chemical composition of the bioactive fractions by using high-resolution gas chromatography and GC-MS - Coqueiro, Aline [UNESP]; Regasini, Luis O. [UNESP]; Leme, Gabriel M. [UNESP]; Polese, Luciana [UNESP]; Nogueira, Camila T. [UNESP]; Del Cistia, Mayara L. [UNESP]; Graminha, Márcia Aparecida Silva [UNESP]; Bolzani, Vanderlan Da S. [UNESP] (Sociedade Brasileira de Química, 2014)
As part of our ongoing SisBiota CNPq/FAPESP and Biota-FAPESP bioprospecting programs, this paper deals with the leishmanicidal properties of Brosimum glaziovii (Moraceae), and used gas chromatography analysis to determine the chemical composition of these fractions. The extracts and fractions from the leaves and branches of B. glaziovii were screened against Leishmania amazonensis. The hexane fractions from the leaves and branches displayed the highest leishmanicidal activities, with IC50 = 3.6 and 39.1 µg mL-1. Using gas chromatography analysis it was possible to identify the sterols campesterol, stigmasterol, and β-sitosterol, as well as the triterpenes α-amyrin, β-amyrin, β-amyrin acetate, and lupenone, and other nonpolar components, mainly fatty acids and their derivatives. This is the first report on the leishmanicidal activity and the chemical composition of B. Glaziovii.

Dando continuidade às pesquisas de bioprospecção dos programas SisBiota CNPq/FAPESP e Biota-FAPESP, o presente artigo descreve os resultados de atividade leishmanicida e determinação da composição química das frações ativas de Brosimum glaziovii (Moraceae), por meio da cromatografia gasosa. Os extratos e frações das folhas e galhos foram testados in vitro em cepas de Leishmania amazonensis. As frações hexânicas das folhas e galhos apresentaram atividades potente e moderada, respectivamente (IC50 = 3,6 e 39,1 µg mL-1). Por meio das análises de cromatografia gasosa foi possível identificar os esteróis: campesterol, β-sitosterol e estigmasterol e os triterpenos: α-amirina, β-amirina, acetato de β-amirina, e lupenona, além de outros constituintes apolares principalmente ácidos graxos e seus derivados. Este é o primeiro trabalho descrito sobre a atividade leishmanicida e composição química desta espécie.
Keywords: Brosimum glaziovii; leishmanicidal; sterol; triterpene; gas chromatography